PERBAIKAN DAN PEMELIHARAAN MOTOR LISTRIK PENGGERAK WATER JET PUMP DI AREA WASTE HEAT RECOVERY SYSTEM PT CEMINDO GEMILANG - Feri Febrian Syah; Endi Permata (JURAL RISET RUMPUN ILMU TEKNIK, 2022)
Electricity is one of the vital needs that is indispensable for all humans and other places, one of which is PT. Cemindo Gemilang, engaged in the cement-producing industry, requires a huge electricity capacity. To reduce or reduce the cost of electrical energy, a power plant unit and a WHRS (waste heats recovery system) were made to supply electrical energy to the cement plant area. PT. Cemindo Gemilang and the Power Plant rely heavily on electric motors, almost all of which operate using electric motors. The electric motor is a single-phase or three-phase type with a voltage of 11 KV, 6.6 KV or 400 volts. When all generating units operate, all electric motors that play an essential role will continue to be active so that damage is often caused by operation and service life therefore in the power plant department, and there is an electrical and mechanical maintenance division to maintain the continuity of the power plant operational system. This study's aim 1). Explain about electric motors, 2). Explain the definition of the water jet pump, 3). Explain how the water jet pump works 4). Explain the components used in electric motors and their repair and maintenance.